Focal point analysis of torsional isomers of acrylic acid - ÇİFTÇİOĞLU, GÖKÇEN ALEV; YAVUZ, İLHAN (TAYLOR & FRANCIS LTD, 2010)
The thermochemistry of acrylic acid has presented challenges owing to its high reactivity, tendency to dimerize in the gas phase, and the existence of two very nearly equal energy conformational isomers. Well-tested thermochemical schemes including G2, G3, G4, and CBS-QB3 agree in the prediction that the s-cis syn structure is the most stable of the torsional isomers, with the s-cis anti form lying 3 kJ mol-1 or less higher in energy. Microwave spectra suggest a value of 0.63 kJ mol-1. The energy barrier between these forms is in the neighbourhood of 25 kJ mol-1 according to a MP2/cc-pVDZ calculation. We present estimates of the relative energies of all four torsional isomers and the rotational barrier based on a variant of the Focal Point Analysis developed by Csaszar and co-workers. These calculations, extending to the CCSD(T)/cc-pV5Z level, predict that the s-cis anti torsional isomer is the most stable form, in contrast to prior estimates. The s-cis syn form lies about 2.9 kJ mol-1 higher, while the s-trans syn and anti forms lie at about 21.7 and 23.3 kJ mol-1, respectively. We estimate the rotational barrier between the s-cis trans and s-cis anti structures to be about 23.9 kJ mol-1. Error ranges derived from the fit to extrapolation forms suggest that our estimates have an uncertainty of about 0.1 kJ mol-1.
Keywords: thermochemistry; focal point analysis; conformational energy; extrapolation methods; COMPLETE BASIS-SET; AB-INITIO; GAUSSIAN-2 THEORY; MODEL CHEMISTRY; SYSTEMATIC SEQUENCES; ROTATIONAL-ISOMERISM; WAVE-FUNCTIONS; ATOMS; MOLECULES; ACCURACY